Single atom tungsten doped ultrathin α-Ni(OH)2 for enhanced electrocatalytic water oxidation - Yan, Junqing; Kong, Lingqiao; Ji, Yujin; White, Jai; Li, Youyong; Zhang, Jing; An, Pengfei; Liu, Shengzhong; Lee, Shuit-Tong; Ma, Tianyi (Nature communications, 2019)
Electrocatalytic water oxidation is a rate-determining step in the water splitting reaction. Here, we report one single atom W 6+ doped Ni(OH) 2 nanosheet sample (w-Ni(OH) 2 ) with an outstanding oxygen evolution reaction (OER) performance that is, in a 1 M KOH medium, an overpotential of 237 mV is obtained reaching a current density of 10 mA/cm 2 . Moreover, at high current density of 80 mA/cm 2 , the overpotential value is 267 mV. The corresponding Tafel slope is measured to be 33 mV/dec. The d 0 W 6+ atom with a low spin-state has more outermost vacant orbitals, resulting in more water and OH − groups being adsorbed on the exposed W sites of the Ni(OH) 2 nanosheet. Density functional theory (DFT) calculations confirm that the O radical and O-O coupling are both generated at the same site of W 6+ . This work demonstrates that W 6+ doping can promote the electrocatalytic water oxidation activity of Ni(OH) 2 with the highest performance. Electrocatalytic water splitting for hydrogen and oxygen generation provides an attractive path to obtain clean energy, but the half reaction of oxygen evolution remains the bottleneck for the progress. Here, the authors show single atom tungsten doped ultrathin α-Ni(OH) 2 exhibits enhanced performance in electrocatalytic water oxidation.